Konseling Kelompok Rational Emotive Behavior Therapy: Sebuah Alternatif dalam Mengatasi Stres Akademik pada Mahasiswa - Ade Herdian Putra; Netrawati Netrawati; Yeni Karneli (SCHOULID: Indonesian Journal of School Counseling)
Online lectures conducted when the COVID-19 pandemic hit Indonesia caused various problems, especially for students. One of the problems that arise in students is experiencing academic stress. Academic stress experienced by students in attending online lectures occurs due to the inability of students to meet the demands of online lectures. Academic stress experienced by students in attending online lectures is basically caused by irrational beliefs about online lectures, giving rise to negative perceptions of online lectures. One alternative in dealing with student academic stress in attending online lectures is through group counseling using the Rational Emotive Behavior Therapy approach. This research uses a literature study approach. The author explores the literature related to academic stress and group counseling using the Rational Emotive Behavior Therapy approach. This article describes Rational Emotive Behavior Therapy group counseling as an alternative in dealing with student academic stress in attending online lectures.